(untitled) (CAHIERS MAGELLANES-NS, 2024)
This study evaluates the efficacy of yoga therapy in managing lumbar pain among geriatric men. A sample of 40 participants was divided into two groups, one receiving yoga therapy and the other receiving standard care. Pain levels were measured before and after a 12 weeks period using a standardized assessment tool. ANOVA analysis revealed significant differences between the groups, with the yoga therapy group showing greater pain reduction. These findings suggest that yoga therapy is a viable option for managing lumbar pain in Geriatric men.